2007
DOI: 10.4049/jimmunol.178.5.2706
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cells Amplify the Innate Immune Response to Lipopolysaccharide

Abstract: NKT cells are thought of as a bridge between innate and adaptive immunity. In this study, we demonstrate that mouse NKT cells are activated in response to Escherichia coli LPS, and produce IFN-γ, but not IL-4, although activation through their TCR typically induces both IL-4 and IFN-γ production. IFN-γ production by NKT cells is dependent on LPS-induced IL-12 and IL-18 from APC. LPS induced IFN-γ production by NKT cells does not require CD1d-mediated presentation of an endogenous Ag and exposure to a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
268
3
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(302 citation statements)
references
References 40 publications
(41 reference statements)
22
268
3
9
Order By: Relevance
“…Several studies have demonstrated that NKT cells promote LPS-or cecal ligation and puncture (CLP)-induced sepsis in mice through the production of IFN-γ [8][9][10]. Consistent with these findings, two independent studies have demonstrated that treatment of C57BL/6 mice with anti-CD1d antibody enhances survival rates during CLP-induced sepsis [11,12], suggesting that NKT-cell-mediated promotion of sepsis depends on an interaction between CD1d and TCRs of NKT cells.…”
Section: Introductionsupporting
confidence: 68%
“…Several studies have demonstrated that NKT cells promote LPS-or cecal ligation and puncture (CLP)-induced sepsis in mice through the production of IFN-γ [8][9][10]. Consistent with these findings, two independent studies have demonstrated that treatment of C57BL/6 mice with anti-CD1d antibody enhances survival rates during CLP-induced sepsis [11,12], suggesting that NKT-cell-mediated promotion of sepsis depends on an interaction between CD1d and TCRs of NKT cells.…”
Section: Introductionsupporting
confidence: 68%
“…In the context of sterile inflammation, iNKT cells can have deleterious effects on local and systemic responses. For example, iNKT cells strongly participate in hepatitis induced by concanavalin A 54,68 and ␣-GalCer, 69,70 in hepatic reperfusion injury, 71,72 and in lipopolysaccharide-induced 73 or cecal ligation and puncture-mediated 74 acute septic shock. We evaluated their potential regulatory function in DENV-induced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of a-Galcer increases migration of lamina propriadendritic cells (LP-DCs) to mesenteric lymph nodes, which is suggestive of increased CCR7 expression by LP-DCs [35]. Furthermore, LP-DC activation can be enhanced through cytokine production by activated iNKT cells [36]. Depending on the nature of the APC presenting a-Galcer, specific cytokines are secreted by the activated iNKT cell [37], a finding which could be harnessed in novel immunomodulatory strategies.…”
Section: Inkt Cellsmentioning
confidence: 99%
“…More recently Lee et al [46] characterized circulating MAIT cells in a large sample of 133 healthy adults and reported high variability in circulating MAIT cell numbers across subjects (0.19-21.7%). Although no significant differences in numbers between males and females were found there was a significant decrease in MAIT cell numbers in elderly subjects (n = 45, ages 61-92) versus young subjects (n = 44, ages [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Characteristics Of Mait Cellsmentioning
confidence: 99%